IMPLEMENTASI LIVEWORKSHEET-WEB BASED UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS - Denok Febrianingrum; I Nyoman Ruja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to describe the implementation of Liveworksheet, a web-based platform, in contributing to the development of students' interest and motivation in Social Studies (IPS) learning. This study is motivated by the low enthusiasm and spirit among students during the learning process, which negatively impacts their academic achievement. The lack of variety in learning media often leads to student boredom and disinterest, particularly in Social Studies, a subject frequently perceived as monotonous. Therefore, there is a need for innovative, interactive, and engaging learning media to encourage active student participation. This research employs a qualitative descriptive method, using data collection techniques such as direct observation, in-depth interviews, and documentation. The subjects of this study are seventh-grade students (Class VII.2) at the junior high school (SMP) level. The findings reveal that the integration of web-based Liveworksheet significantly enhances students' learning interest, promotes their active participation during lessons, and fosters both intrinsic and extrinsic motivation. This media encourages students to be more active, communicative, and enthusiastic in engaging with Social Studies material. Furthermore, the interactive presentation of content through Liveworksheet helps students understand key concepts more enjoyably and effectively. In conclusion, the use of Liveworksheet as a learning medium is considered an effective strategy to increase students’ interest and motivation in Social Studies learning at the junior high school level.